PENGUKURAN KUALITAS AIR DOMESTIK DI RUMAH WARGA KELURAHAN BESAR, KECAMATAN MEDAN LABUHAN KOTA MEDAN - Luthfi Parinduri; Saypul Bahri; Cahya Putra Wibowo; Muhammad Age Rianto; Muhammad Fahreza; Rizki Wijaya Sirait; Aulia Maya Fahira Lubis; Fachrun Fikriyyah; Khairani Nasution; Sakinah Eprilia; Andi Syahputra; Kelana Sultan; M. Ikhsan Harahap; Intan Syahdila Febriandini (Jurnal Pengabdian Mitra Masyarakat, 2023)
Kelurahan Besar is one of the sub-districts in Medan Labuhan District, Medan, North Sumatra, Indonesia with an area of 6,000 km2. Kelurahan Besar itself is surrounded by many industries which happen to be in the Medan Industrial Estate (KIM) area, besides that there are warehouse areas, business centers and residential areas. Both positive and negative impacts will be felt by residents. One of them is the condition and quality of clean water used by community members who are concerned that they have been exposed to organic waste from the production process produced by Industrial Estate activities. There are those who think that clear water when seen by naked eye, is definitely safe to use. Even though not all clear water is suitable for use. To ensure that water is suitable for use, it is necessary to carry out laboratory tests. Measurements and observations were made on several water quality parameters (Hydrogen Potential, Salinity (Total Dissolved Solid / TDS), Total Suspended Solid (TSS), Water Color, Turbidity, Conductivity and COD (based on KMnO4 Factor) from water samples taken The results show that water from wells used by residents to meet their daily needs is safe to use because no trace outspecs were found.